Social interaction among tinder users on sexual dating during movement control order / Mohd Yusof Zulkefli … [et al.] - Zulkefli, Mohd Yusof; Sahharon, Hamizah; Redzuan, Ahmad (Faculty of Communication and Media Studies (FCMS), 2023)
Staying on a social basis does not mean people must cancel their social plans. Instead, a person itself needs to adjust them a bit. Tinder is one of the online interaction platforms that has provided an alternative and effective way for social interaction among society members. Tinder has a minimum of 10 million active users and is a widely used mobile dating application that enables users to date online, especially during the Movement Control Order (MCO). Unfortunately, the pandemic has also snatched away the connections that feed passion, contentment, belonging and all other variations of physical love. This research explores the social interaction among Tinder users on sexual courting during the MCO. Since this is exploratory research, therefore a qualitative research paradigm is used in this research. The data was obtained by using purposive sampling through an in-depth interview. Most users were involved in sexual courting on Tinder during MCO since they are alone, and it is the only way for them to find someone to talk to fill the loneliness. In terms of social interaction style, male Tinder users are more likely to seek relationships and sexual relationships through sexual courting. However, female users tend to be reserved and involved in sexual courting. The research findings can serve as a guideline for society members, especially young adults, to prevent them from falling into the sexual trap.